Polarization properties of the Vavilov-Cherenkov radiation - Afanasiev, G.N.; Lyubchenko, M.V.; Stepanovsky, Yu.P. (Вопросы атомной науки и техники, 2007)
We consider polarization properties of the Vavilov-Cherenkov radiation using the relativistic quantum treatment of the one-photon Cherenkov emission. The probability of the one-photon emission by relativistic electron is calculated in the framework of quantum electrodynamics with inclusion of all polarizations (polarized electron 1 emits polarized electron 2 and polarized γ-quantum). Relations between initial and final electron polarizations were found. Розглянуті поляризаційні властивості випромінювання Вавілова-Черенкова. У межах квантової електродинаміки з урахуванням всіх поляризацій розрахована ймовірність однофотонного процесу. Знайдене співвідношення між поляризаціями початкового і кінцевого електрона. Рассмотрены поляризационные свойства излучения Вавилова-Черенкова. В рамках квантовой электродинамики с учётом всех поляризаций рассчитана вероятность однофотонного процесса. Найдено соотношение между поляризациями начального и конечного электрона.